Um modelo exploratório, baseado nas comunidades Linux, para desenvolvimento da tecnologia da informação no Brasil - Motta, Luiz Carlos do Carmo (2002)
The present work aIms at building an Exploratory Model for the development of information technology, applicable in Brazil, having as a reference the Linux community work and production organization forms. The Model should be applied in the Internet environrnent or in other telecommunication networks. To such aim, it uses distance leaming and e-Iearning methods and techniques. Model construction is based, for its major theoretical foundation, on Illich's (1976) conviviality concept, on the understanding of Inose and Pierce (1984) on interested communities and software democratization, on the studies of Malone (1997, 1998) pertinent to network organization models, on the studies of Weber (2000) about online interested communities, on the 'Digital Thinking' enabling methodology by Joia (1999-1, 1999-2) and on the pedagogical - methodological strategy of the Australian National Training Authority (TAFE/SA). However, Matesco's research (2000, 2001) have made the idea of Model construction feasible, having in mind that the proposed Exploratory Model applies, preferably, to countries, regions, enterprises, or organizations which depend technologically on their business partners, and which bear scarce resources to invest in research and development. The methodological path to Model construction starts with a short approach on the Linux operational system and on the description of the forms of organization of the work and production in F ordism-Taylorism and in Post-Fordism. It sites the functioning of Linux communities in regard to these forms of organization. It proceeds by describing the process of knowledge formation in distance learning and in e-Iearning. It approaches the experience of other countries with Linux and with the Linux communities. ~lainly the success achieved by the Nordic countries in the absorption of technology. After that, based on two research works by Matesco (2000, 2001), it analyses Brazil's technological dependence and proposes the Exploratory Model, whose objective is, to prioritarily collaborate toward the reduction of this dependence by means of a knowledge-formation process, based on distance learning and e-Iearning of Linux and on the propagation of Linux communities, by employing the network organization mode!.